Pengaruh Gaya Kepemimpinan dan Komunikasi Interpersonal terhadap Kinerja Karyawan dengan Semangat Kerja sebagai Variabel Intervening pada PT. Agromuko Sei Betung Estate - Hati, Rita (Lembaga Yasin AlSys, 2026)
Employee performance is a strategic factor in the operational success of plantation companies, particularly in work units responsible for achieving production targets; however, studies that specifically examine the influence of leadership style and interpersonal communication on employee performance with work motivation as an intervening variable in the context of oil palm plantations, especially at PT. Agromuko Sei Betung Estate, remain limited. This study aimed to analyze the influence of leadership style and interpersonal communication on employee performance with work motivation as an intervening variable among employees of Division 1 at PT. Agromuko Sei Betung Estate. A quantitative approach with an explanatory survey design was employed, involving 96 respondents selected using a saturated sampling technique. Data were collected using a five-point Likert scale questionnaire, supported by observations and interviews to enrich the contextual understanding of the findings, and were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS software. The results showed that leadership style and interpersonal communication had a significant effect on work motivation, and that leadership style and work motivation had a significant effect on employee performance. Interpersonal communication did not have a significant direct effect on performance but had a significant indirect effect through work motivation, thereby reinforcing the role of work motivation as a mediating mechanism in enhancing employee performance. These findings indicate that strengthening effective leadership practices and a constructive internal communication culture constitutes an important strategy for companies to improve work motivation and employee performance in oil palm plantation units.